(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
The main aim of the project was to carry out excavations in Kelso and Jedburgh at sites which were due to be developed. Excavations were also carried out in Eyemouth, Stow and Peebles. Reports on excavations in Jedburgh, Bishop’s Palace. Stowe and springwood Park have been produced separately.